2014
DOI: 10.1002/anie.201407359
|View full text |Cite
|
Sign up to set email alerts
|

π Aromaticity and Three‐Dimensional Aromaticity: Two sides of the Same Coin?

Abstract: A bridge between classical organic polycyclic aromatic hydrocarbons (PAH) and closo borohydride clusters is established by showing that they share a common origin regulated by the number of valence electrons in an electronic confined space. Application of the proposed electronic confined space analogy (ECSA) method to archetypal PAHs leads to the conclusion that the 4n+2 Wade-Mingos rule for three-dimensional closo boranes is equivalent to the (4n+2)π Hückel rule for two-dimensional PAHs. More importantly, use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
176
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 268 publications
(177 citation statements)
references
References 49 publications
0
176
0
1
Order By: Relevance
“…The presence of chloride-anions and solvent molecules can effect complexation reactions: they are able to replace other ligands in metal coordination sphere, and the resulting metal/ligands ratio in the obtained products does not correspond to the initial molar ratio of reagents. Complexes [Co(phen) 2 Cl(H 2 O)]Cl [13] and abovementioned [Co(m-NBh) 4 ] (n = 10, 12) was proved by X-ray diffraction; first cobalt(II) compounds with perchlorinated closodecaborate anion and cobalt(III) complex with the closo-dodecaborate anion were synthesized and structurally characterized.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of chloride-anions and solvent molecules can effect complexation reactions: they are able to replace other ligands in metal coordination sphere, and the resulting metal/ligands ratio in the obtained products does not correspond to the initial molar ratio of reagents. Complexes [Co(phen) 2 Cl(H 2 O)]Cl [13] and abovementioned [Co(m-NBh) 4 ] (n = 10, 12) was proved by X-ray diffraction; first cobalt(II) compounds with perchlorinated closodecaborate anion and cobalt(III) complex with the closo-dodecaborate anion were synthesized and structurally characterized.…”
Section: Introductionmentioning
confidence: 97%
“…Besides, the boron cluster anions form numerous polymeric or mononuclear complexes with such metals as Pb, Cu, Ag, Au, Zn, Cd, Hg, etc [3]. Although these are compounds with electron-deficient bonds [4], they can form in addition to coordination bonds a wide set of specific B-H. . .H(X) (X = N, O, C) interactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it was shown by Poater et al that classical organic polycyclic aromatic hydrocarbons (PAH) and closo-borohydride clusters share a common origin regulated by the number of valence electrons in an electronic confined space. [13] Different cases of boron homocatenated compounds stabilized by lithium and hydrogen atoms were theoretically tested. [14] A number of theoretical studies on different compounds mimicking common organic species is reported elsewhere.…”
mentioning
confidence: 99%
“…[10][11][12] Furthermore, the link between hydrocarbons and borohydrides has also been analyzed, finding that these compounds share a common root regulated by the number of valence electrons in a confined space. [13][14] Interestingly, these authors demonstrated the existence of a relation between planar aromatic annulenes and tridimensional aromatic closo boron hydride clusters. 15 These results seem to indicate that the IS principle applies effectively when designing boron analogues of aromatic organic compounds.…”
Section: Introductionmentioning
confidence: 99%